ANALISIS KESULITAN SISWA DALAM MENYELESAIKAN SOAL FISIKA MATERI USAHA DAN ENERGI DI SMP - Sari, Giarti Puspita; Tandililing, Edy; Oktavianty, Erwina (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Â AbstractThis research aims to reveal profile, theÂ  percentage and find out the causes of students having difficulty in solving about work and energy. Research conducted at SMPN 12 Pontianak with research subjects wAere 73 students. Data collected by the test essay and interviews. The analysis data technic that did was Miles and Huberman. The results show that students' difficulties are divided into 5 according to the Heller problem solving stages. (1) Difficulty of visualize the problems experienced by students was 95.62%. The cause is because students do not know to draw sketches on the problems. (2) The difficulty of physics description experienced by students was 55.06%. The cause is lack of understanding of the problem given. (3) The difficulty of the plan a solution experienced by students was 47.12%. The cause is lack of understanding of the concept used. (4) While the difficulty of execute the plan experienced by students was 52.06%. Because it is wrong to write down and be asked, it causes students to have difficulty carrying out the plan. (5) And difficulties check and evaluate was 53.43%. The cause is because the students are less careful in checking the answers.Keywords: analysis difficulty, problem solving Heller, work and energy